Panel Summary: Defining the Mental Health and Addictions 'Basket of Core Services' to be Publicly Funded in Ontario - Bullock, Heather; Waddell, K; Wilson, MG (My University, 2016)
A summary of what was learned from a citizen panel that addressed problems related to mental health and addictions, options for addressing these problems, key implementation considerations, and next steps for generating a basket of core mental health and addiction services for Ontario.
Keywords: mental; health; addictions; basket; core; services; Ontario